Modelling and Experimental Testing of Passive Magnetic Bearings for Power Loss Reduction - Alessandro Vigliani; Salvatore Paolo Cavallaro; Simone Venturini (Applied Sciences)
The development of rotordynamic systems with reduced energy dissipation is a key challenge in modern applications, such as Flywheel Energy Storage Systems. This paper investigates a fully passive vertical rotor system supported by two passive magnetic bearings whose configuration provides radial stability while minimising power losses due to their thrust effect. A numerical model describes the forces and stiffness of the magnetic bearings, identifying the operational range of the thrust–radial support configuration. A test rig is developed for the experimental characterisation of the rotor and passive magnetic bearings in both static and dynamic conditions. Different magnetic thrust force levels are tested by varying the axial distance between the rotor and stator magnetic rings of the bearings. Static tests are performed to measure the weight force compensation corresponding to the different bearing configurations, validating the numerical model. Dynamic tests analyse the rotor power losses with a non-invasive approach via optical sensor measurements.